2009
DOI: 10.1089/jmf.2008.1011
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Analgesic Effects of the Aqueous Extract of Corni Fructus in Murine RAW 264.7 Macrophage Cells

Abstract: Corni fructus is the fruit of Cornus officinalis Sieb. et Zucc, which is classified into the dogwood family of Cornaceae. Corni fructus has antineoplastic, antioxidative, and antidiabetic effects, but its anti-inflammatory and analgesic effects are unknown. Here, we investigated the anti-inflammatory and analgesic effects of an aqueous extract of corni fructus using murine RAW 264.7 macrophage cells. For this study, we used the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay, western blot an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 34 publications
1
30
0
3
Order By: Relevance
“…Use of C. officinalis was first recorded in Shen Nong's Materia Medica approximately 2,000 years ago in China. It was recently reported C. officinalis possesses immune regulating function, anti-oxidative, anti-diabetic and anti-inflammatory effects [12][13][14]. Cornel iridoid glycoside (CIG), the principal active component of this herb, was recently reported to have anti-inflammatory effect sufficient to prevent the over-expression of transforming growth factorb1 and the over-deposition of glomerular matrixes in an experimental model of diabetes [15].…”
Section: Introductionmentioning
confidence: 99%
“…Use of C. officinalis was first recorded in Shen Nong's Materia Medica approximately 2,000 years ago in China. It was recently reported C. officinalis possesses immune regulating function, anti-oxidative, anti-diabetic and anti-inflammatory effects [12][13][14]. Cornel iridoid glycoside (CIG), the principal active component of this herb, was recently reported to have anti-inflammatory effect sufficient to prevent the over-expression of transforming growth factorb1 and the over-deposition of glomerular matrixes in an experimental model of diabetes [15].…”
Section: Introductionmentioning
confidence: 99%
“…A crude extract of the fruit of Cornus officinalis has been reported to process such pharmacological actions as anti-neoplasm, anti-inflammation, and anti-diabetes. [9][10][11] Studies have also indicated that cornuside can suppress the expression of cytokine-induced proinflammatory and adhesion molecules in human endothelial cells, and can protect cultured rat cortical cells against damage induced by oxygen-glucose deprivation, 12,13) but there is little information on the pharmacological action of cornuside in acute liver injury caused by CCl 4 . This study was undertaken to evaluate the protective effects of cornuside on CCl 4 -induced hepatotoxicity and to elucidate the possible mechanisms underlying these protective effects in rats.…”
mentioning
confidence: 99%
“…All these results had a synergic effect when used with ciprofloxacin. WSY-1075 is composed of C. fructus, A. gigantis radix, L. fructus, C. parvum cornu, G. radix rubra, and C. cortkex [8,9,[14][15][16].…”
Section: Discussionmentioning
confidence: 99%